Modeling and Deploying RESTful Services with SOMF-Based SOA: A Case Study in the Credit Guarantee Industry - Ramdhani, Amrid; Nilo Legowo (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2025)
The integration of electronic systems across financial institutions poses significant challenges, particularly when legacy architectures rely on siloed, point-to-point connections. This often leads to what is commonly known as "spaghetti integration," where changes in one system can trigger unintended disruptions in others. This study addresses such integration issues within the Kredit Usaha Rakyat (KUR) credit guarantee service of an Indonesian credit guarantee institution by implementing a Service-Oriented Architecture (SOA) approach, guided by the Service-Oriented Modeling Framework (SOMF). This study aims to improve system performance, scalability, and regulatory adaptability through a structured, multi-phase methodology based on SOMF: conceptualization, discovery and analysis, business integration, logical design, and logical architecture. Data for the study were drawn from system documentation, national regulatory requirements (e.g., Coordinating Minister Regulation No. 1/2023), and the evaluation of service interactions via RESTful APIs using lightweight JSON formatting. These findings demonstrate that the adoption of SOA with SOMF enables the development of modular, interoperable, and adaptable services. This approach reduces redundant processes, enhances real-time data flow, and strengthens integration between the guarantee institution and its partner banks. The resulting system aligns with modern digital governance requirements and provides a sustainable foundation for future growth and compliance.